Pengaruh Perubahan Bank Umum Syariah Terhadap Minat Menabung di Bank Aceh Syariah Pada Masyarakat Kabupaten Aceh Tenggara - Asra Idriyanssyah Purba (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
This study aims to know the reaction of the community and how much influence the operational changes of the Aceh bank from the conventional system to the Is system. And how big the influence of change to Islamic Commercial Bank in terms of factors Religion, economy and Information on the interest of saving in Southeast Aceh society. This study uses a quantitative method involving 100 people from various backgrounds in Southeast Aceh. The results showed that the factor of Religion and Information affect the interest of saving in the bank of Aceh Islamic while the economic factor is very big influence on the interest of saving in the Aceh Islamic Bank. This means that people judge economic factors give a big influence on the public interest to save in Islamic bank (Aceh Islamic Bank)